Ecological Risk Assessment of Consuming Vegetables Exposed To Heavy Metals From Hairdressing Salon - Dike, Nwanne Ijere; Ukachukwu, Chidinma Ogochukwu; Udebuani, Angel Chika; Ugwu, Tochukwu Nicholas; Abara, Priscillia Nkeonye; Enesi, Katumi Ohunene (International Journal on Food, Agriculture and Natural Resources, 2025)
This study is focused on the impact of improper disposal of hair dressing contaminated water on farmland within different communities. Presence of different heavy metals were detected at Ohofia and Isiukwuto communities while, Talinum triangulare and Telfairer occindentalis were planted in the soil obtained from sampling sites. Health risk, ecological risk and bioaccumulation factor was estimated on the plants. Different heavy metals were accumulated in the plants. However, iron was highest in both T. triangulare and T. occidentalis with value of 109.92 and 48.84 respectively. The bioaccumulation factor of plants was in this order Fe < Cd< Mn < Cr < Zn < Ni < Cu < As < Pb < Hg respectively. Besides, Fe is considered to be of high ecological risk concerns (160 ≤ Eir < 320). While, the health risk showed that the ten heavy metals detected exceeded the non-carcinogenic risk (I.e. THQ >1) though, in Isiukwuato Fe appears to have highest THQ (target hazard quotient). The ecological risk perceived in the assessment indicates that hair dressing salon waste contamination of arable soil and farmland is unsafe. Therefore, effective and safe method is required for proper discharge.